Do We Know How Much Poverty There Is? - Miguel Székely; Nora Lustig; Martin Cumpa; José Antonio Mejía-Guerra (Inter-American Development Bank, Research Department, 2000)
This paper tests the sensitivity of poverty indexes to the choice of adult equivalence scales, assumptions about the existence of economies of scale in consumption, methods for treating missing and zero incomes, and different adjustments to handle income misreporting. We also perform sensitivity analysis to the use of different poverty lines and poverty indexes, which are issues that have been much more explored in the literature. The sensitivity analysis is applied to household survey data from 17 Latin American countries, which include 92% of the population in the region. By varying these parameters within reasonable boundaries, we find that the proportion of poor could be said to be either 12. 7 percent or 65. 8 percent of the total population. Additionally, the ranking of countries with respect to poverty is also highly sensitive. This points to the need of justifying and being explicit about the underlying choices and definitions behind poverty statistics, and to the need of performing sensitivity analysis illustrating the menu of options that can answer the question of how much poverty there is.
Keywords: 330; Armut; Messung; Grundbedürfnisse; Vergleich; Lateinamerika